PENGARUH IMPLEMENTASI SISTEM AKUNTABILITAS KINERJA INSTANSI PEMERINTAH (SAKIP) TERHADAP PENERAPAN GOOD GOVERNANCE - BADRUZAMAN1, JAJANG; CHAIRUNNISA, IRNA (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 7 No 1 (2012))
This research aims to study (1) the implementation of accountability system of government institution performance in 14 Local Departments in Ciamis Government Regency, (2) the aplication of good governance in 14 Local Departments in Ciamis Government Regency, and (3) the influence of implementation of accountability system of government institution performnace on the aplication of good governance in 14 Local Departments in Ciamis Government Regency. The research method used is descriptive method with cencus approach. Analysis method used is correlations coefficient analysis and determination coefficient analysis to process data collected using questionnairy survey. The result shows that (1) the implementation of accountability system of government institution performance in 14 local departments in Ciamis Government Regency is good, (2) the aplication of good governance in 14 local departments in Ciamis Government Regency is good, and (3) the implementation of accountability system of government institution performance has a strong correlations with the aplication of good governance in 14 local departments in Ciamis Government Regency.
Keywords: accountability system of government institution performance, good governance, Ciamis Government Regency